Statues and Storms: Leading through Change - Chisholm, Linda (New Agenda: South African Journal of Social and Economic Policy, 2024)
Not thirty, but twenty years after democracy, South Africa’s oldest and most prestigious university was wracked by tumultuous upheavals sustained over two long years between 2015 and 2017. Although contestation and challenge were not new to the university, the nature and degree of student protest, directed at the university itself, were. A few years later, Max Price’s successor, Mamokgethi Phakeng, experienced different storms that relegated the events of 2015-7 firmly to the past. The book is nonetheless still relevant, as the calls with which those years were associated, for ‘free, quality, decolonial education,’ have endured.